KONTRIBUSI ILMU TASAWUF DALAM PEMBANGUNAN KARAKTER BANGSA - As, Asmaran (Jurnal Studia Insania, 2014)
Sufism is a pure consciousness that is able to direct the human?s soul to be good one and has a noble attitude and one of the most things in determining of a person?s behavior is the one?s own desires. Lust basically should not be turned off, but it must be controlled and directed to conduct an appreciable act. In order to make the soul has such a feeling, it takes hard efforts to turn the nature on that Allah swt has given since he was still in the spiritual realm. In character development, the people in Sufism said that there are stages that must be passed are tathahhur, tahaqquq and takhalluq, or in other terms with similar meaning, namely takhalli, tahalli, and tajalli.